BP plc 2010 – a case of linguistic legitimation?. Issue 4 (13th November 2017) - D'Northwood, Gavin
Abstract : Purpose: The purpose of this paper is to examine the statements by the chairman and CEO in BP plc's Annual Report 2010 for linguistic evidence of reader positioning. This is based on the premise that reputational fallout from the Deepwater Horizon oil spill would have heightened the need for such positioning to repair the company's legitimacy. Design/methodology/approach: Applying Halliday's systemic functional linguistics (SFL) framework, a comparative register analysis was undertaken of the respective statements of the chairman and CEO of BP plc. This was informed by corpus analysis of these statements, of comparative statements from industry competitors and of two larger-scale corpora constructed from the chairman and CEO statements extracted from the annual reports of 25 FTSE100 companies. Findings: The findings suggest that readers' perceptions are likely to be shaped by the statements of the chairman and CEO of BP plc in the company's 2010 annual report, but similarities and differences are apparent in the way this positioning is engineered. Broader corpus analysis hints that these similarities and differences are not localised to BP plc. Research limitations/implications: The analysis relies on the assumptions that the chairman and CEO are the writers of each piece. As with prior research, questions of intent on the part of the corporate authors and impact upon target readers remain unanswered. Practical implications: This paper demonstrates and highlights the issue of reader positioning through lexico-grammatical choices in corporate disclosures. Originality/value: This paper makes a contribution to the literature by demonstrating how reader positioning may be engineered through lexico-grammatical choices in corporate disclosures. This paper further responds to a call from Sydserff and Weetman (1999, 2002) for interdisciplinary approaches to investigating corporate narrative reports involving linguistics, through foregrounding Halliday's SFL framework as an analytical tool.